The effect of seed inoculation with arbuscular mycorrhizal fungi on some chemical characteristics and seed germination of corn (SC704) under drought stress - Ahmad Afkari (علوم و فناوری بذر ایران)
In order to investigate the effects of seed inoculation with arbuscular mycorrhizal fungi on some chemical characteristics and seed germination of corn (Zea mays L.) under drought stress conditoins, a factorial experiment based on randomized complete design with three replications was conducted at the physiology laboratory of Islamic Azad University Branch Ardabili, during 2015. Studied factors were: drought stress in four levels (Zero, -4, -8 and -12 bar) and seed inoculation with mycorrhizal fungus in four levels (no inoculation, seed inoculation with Funneliformis mosseae, Rhizoglomus fasciculatum and Claroideoglomu etanicatum. The results showed that the effect of drought stress and seeds inoculation with mycorrhizal fungi on germination components, seed protein content and antioxidant enzymes was significant at 1% probability Level. Seed inoculation with Rhizoglomus fasciculatum showed higher antioxidant enzymes activity and higher seed protein content compared with inoculation with Funneliformis mosseae, Claroideoglomus etanicatum and no inoculation. In drought stress conditions, plants will reduce oxidative stress leads to increased activity of antioxidant enzymes has been. The results of the mean comparison of data showed that with increasing drought stress germigation percen and germination rate index decreased and the means of germination time, increased. With respect to the results of this study, it seems that mycorrhiza fangi by an improvement in water and nutrient absorption, improve plant growth in drought stress condition. Thus, in order to increasing of germination components and chemical characteristics, it can be suggested that seeds inoculation of corn was applied with Rhizoglomus fasciculatum